Pengaruh PDRB, Pengangguran, dan Pendidikan Terhadap Kemiskinan Di Kabupaten Tanah Laut Tahun 2011-2021 - Pratiwi, Khovifah Septi; Sa'roni, Chairul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study was conducted to determine the GRDP (Gross Regional Domestic Product), unemployment, and education that affect poverty in Tanah Laut Districts and which factors have a major influence. This study used secondary data from 2011-2021 and multiple linear regression analysis tools, using test f, Test t, and test R- square (R2). As a result of this study, GRDP and unemployment significantly affected poverty in Tanah Laut Districts, while education didn’t significantly affect poverty in Tanah Laut Districts.